Characterization and antibacterial activity of biogenic iron nanoparticles using Proteus mirabilis - Mais Emad Ahmed; Huda Mohammed Hasan; Anfal Jabbar Kttafah (Medical Journal of Babylon)
Abstract Background: The green production of iron oxide nanoparticles (FeONPs) due to its numerous biotechnological uses has attracted a lot of attention and clean and eco-friendly approaches in the medical field. Objectives: The objectives of this study are to demonstrate the biogenic creation of FeONPs. The search for alternative antimicrobial medicines has been prompted by growing worries about multidrug resistance. Materials and Methods: The purpose of this work was to investigate if Proteus mirabilis was the source of green-manufactured iron nanoparticles (INPs). The Fourier transform infrared, attenuated total reflectance, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, ultraviolet–visible, and dynamic light scattering measurements were used to characterize the green synthesized nanoparticles (NPs). Using the agar-well diffusion method, the antibacterial investigation’s efficacy was evaluated. Results: The results found that at 128 μg/mL minimum inhibitory concentration, we have demonstrated the potent antibacterial properties of FeONPs produced through biological procedures against Gram-positive and Gram-negative bacteria that are resistant to many drugs. These NPs, including their antimicrobial qualities, how they work, how they affect drug-resistant microbes, the risks involved with using them, the unique qualities of NPs, their mode of action as antibacterial properties, and the elements that influence how well they function in a therapeutic setting all are thoroughly investigated. Conclusion: Further research on biogenic INPs was necessary to enhance their nanopharmacological importance for biological applications, as they have demonstrated promising biomedical capabilities were successfully synthesized in a friendly environment with few costs, and the highly INPs product showed exceptional activity against bacterial strains.